Pengaruh Store Atmosphere, Price, Lifestyle Dan Location Terhadap Keputusan Pembelian (Studi pada Konsumen Kopi Soe di Kabupaten Nganjuk) - Selvi Dwi Rahmawati; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine and analyze the effect of store atmosphere, price, life style and location on purchasing decisions at Kopi Soe, Nganjuk Regency. The population in this study are consumers who visit and make purchases at Soe Coffee. The method in data collection used in this study is a questionnaire (questionnaire) which is distributed to 100 respondents who were selected using purposive sampling. In this study, using the SPSS 16 application. Methods in data analysis using the test instrument, normality test, classical assumption test, multiple linear regression analysis, hypothesis testing and the coefficient of determination (R2). Based on the test on the F test, it is concluded that there is a simultaneous influence between store atmospher, price, lifestyle and location on purchasing decisions and the results of the t test indicate that store atmosphere, price, life style and location have a positive and significant effect on purchasing decisions. keywords: store atmospher, price, lifestyle, location, purchase decision